The children of Eve : population and well-being in history - Cain, Louis P.; Paterson, Donald G., 1942- (Malden, MA : Wiley-Blackwell, 2012)
'This book explores contemporary population issues in a historical context. It is a world economic history of demographic change with emphasis on the well-being of the population. Exploring the years since the Middle Ages, this unique book emphasizes the commonality of human experience illustrating how different people, at different times, in varying circumstances, responded to similar economic forces in more of less the same way'--
'The Children of Eve is the first single volume book to bring together general material on population issues, as it explores the subject of contemporary population in a historical context. The book presents a world history of economic and demographic change that ranges broadly over time and space, while simultaneously emphasizing the well-being of the population. By choosing a large canvas, the authors stress the commonality of human experience: that different people, at different times, and in varying circumstances have responded to similar economic forces in more or less the same way. The book highlights the formative population history of Europe and North America over the years since the Middle Ages. Asia and the southern hemisphere are also discussed within the text. The authors have written in non-technical language and successfully maintain the difficult balance of addressing complex issues in a style that doesn't over-simplify the subject, whilst upholding an approach that is accessible to general readers and students. Throughout the text, definitions and short explanations of economic and demographic terminology are presented in separate boxes to enhance ease of use, and each chapter concludes with a bibliography and selected readings.'--
Includes bibliographical references and index.
Keywords: Population -- History; Well-being -- History; Economic history